2009
DOI: 10.1007/s11033-009-9810-1
|View full text |Cite
|
Sign up to set email alerts
|

Two novel cSNPs of weaver gene in Chinese indigenous goat and their associations with milk yield

Abstract: Weaver gene plays an essential physiological role in the function of many organs, including brain, heart, kidney and endocrine cells, and also in the regulation of insulin secretion by glucose and/or neurotransmitters. Thus, weaver gene is an important potential candidate gene effecting on performance traits. The objective of this study was to detect the genetic variation of five loci within weaver gene by PCR-SSCP, DNA sequencing and forced PCR-RFLP methods in 1,019 Chinese indigenous goats. Two novel coding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…We previously reported that one SNP located on exon 4 was associated with milk yield (P = 0.045) (Li et al, 2010). However, no difference was found in milk composition (P > 0.05).…”
Section: Resultsmentioning
confidence: 91%
“…We previously reported that one SNP located on exon 4 was associated with milk yield (P = 0.045) (Li et al, 2010). However, no difference was found in milk composition (P > 0.05).…”
Section: Resultsmentioning
confidence: 91%
“…The identification of genomic variation is a main step for understanding the relationship between genotype and phenotype. Single nucleotide polymorphisms (SNPs) showed potential as molecular markers to link genotypes with desired traits in goats, such as milk quality and quantity [5][6][7], litter size [8,9], growth rate [8,10], fiber quality [11][12][13] and disease resistance [14].…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphism (SNP) markers can be documented to link genotypes to functional phenotypes of interest ( Liao and Lee, 2010 ). Several studies have shown SNPs have potential as molecular markers for cashmere fiber quality ( Lan et al, 2009 ; Zhou et al, 2011 ; Wang et al, 2012 ), milk traits ( Li et al, 2010 ; Hou et al, 2013 ; Zhao et al, 2013 ; Hou et al, 2014 ), litter size ( Chu et al, 2011 ) and growth traits ( Cai et al, 2014 ) in goats. Traditionally, SNP discovery is achieved through comparing sequences of candidate genes or other genomic regions from a number of representative lines or individuals.…”
Section: Introductionmentioning
confidence: 99%